(3bhJ GdbdhH heYGedI GdeMHhHs - (3CHh WGdH Gdecj , eMeO Hf Ydj Hf YWjI GdMGQKj, CHh WGdH Gdecj,J (B386 (3g` s
(3ChdgG (B:s
(3jHOC HPcQ aVGFd GdWgGQI s
(3BNQgG (B:s
(3abO YR bhGai HMQ GdNWGjG hBNQ cGa eY dg CehGL hChMi Gddg JYGdi Edi HYV CfHjGFg dG JJNPhG dg Cgd hGdeGd ai ZjQ GdYbhHGJ Je GdcJGH HMeO Gddg s
(3GdMHQ dhfg HGgJs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B27s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1361s
Keywords: (3GdJUha hGdBOGH GdTQYjIs